2005
DOI: 10.1128/jb.187.2.449-457.2005
|View full text |Cite
|
Sign up to set email alerts
|

Error-Prone DNA Polymerase IV Is Regulated by the Heat Shock Chaperone GroE in Escherichia coli

Abstract: An insertion in the promoter of the operon that encodes the molecular chaperone GroE was isolated as an antimutator for stationary-phase or adaptive mutation. The groE operon consists of two genes, groES and groEL; point mutations in either gene conferred the same phenotype, reducing Lac ؉ adaptive mutation 10-to 20-fold. groE mutant strains had 1/10 the amount of error-prone DNA polymerase IV (Pol IV). In recG ؉ strains, the reduction in Pol IV was sufficient to account for their low rate of adaptive mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 64 publications
4
54
0
Order By: Relevance
“…Previous results have demonstrated that complex cellular pathways regulate both the amount and activity of Pol IV (6,8,12,19,25,26,38,42). The results presented here clarify that RpoS regulates Pol IV directly by altering its amount and indirectly by altering its activity and that these regulatory modes are in effect at different times during the cell cycle.…”
Section: Discussionsupporting
confidence: 57%
“…Previous results have demonstrated that complex cellular pathways regulate both the amount and activity of Pol IV (6,8,12,19,25,26,38,42). The results presented here clarify that RpoS regulates Pol IV directly by altering its amount and indirectly by altering its activity and that these regulatory modes are in effect at different times during the cell cycle.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, the transcription of the dinB gene is controlled by RpoS, a s-subunit of RNA polymerase, which regulates a general stress response (Layton and Foster 2003). PolIV is also regulated by the heat-shock chaperone GroE (Layton and Foster 2005). Therefore, PolIV is a component of several cellular stress responses.…”
mentioning
confidence: 99%
“…Because of this strong phenotype, adaptive mutation in FC40 is often used as an assay for Pol IV's mutagenic activity (e.g., see reference 23). Several factors existent in stationary-phase cells contribute to this high rate of Pol IV-dependent adaptive mutation: (i) transcription of the dinB gene is induced approximately 3-fold under the control of the stationary-phase sigma factor RpoS (42,63), (ii) the Pol IV protein is stabilized by the chaperone GroEL (43), (iii) Pol IV activity is enhanced by cellular polyphosphate (65), and (iv) proposed inhibitors of Pol IV activity, such as UmuD, may be less active or abundant in stationary-phase cells (23). This growth phase regulation suggests that Pol IV's mutagenic activity may serve an important function during nutrient-limited conditions.…”
mentioning
confidence: 99%